Lịch sử phát triển khoa học hành chính - Lê, Thị Vân Hạnh (2011)
Tác giả: Lê Thị Vân Hạnh, TS; Võ Kim Sơn, PGS-TS; Nguyễn Thị Hồng Hải, ThS; Phạm Thu Lan, ThS -- Từ khóa: Khoa học hành chính; Hành chính học